A game of the one attacker against several defenders - Vrublevskaja, I. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: И. Н. Врублевская. Об игре одного нападающего против нескольких защитников I. Vrublevskaja. Vieno puolėjo lošimas prieš keletą gynėjų